Importance of sample volume to the measurement and interpretation of plasma osmolality - Sollanek, Kurt J. (J Clin Lab Anal, 2018)
BACKGROUND: Small sample volumes may artificially elevate plasma osmolality (Posm) measured by freezing point depression. The purpose of this study was to compare two widely different sample volumes of measured Posm (mmol/kg) to each other, and to calculated osmolarity (mmol/L), across a physiological Posm range (~50 mmol/kg). METHODS: Posm was measured using freezing point depression and osmolarity calculated from measures of sodium, glucose, and blood urea nitrogen. The influence of sample volume was investigated by comparing 20 and 250 μL Posm samples (n = 126 pairs). Thirty‐two volunteers were tested multiple times while EUH (n = 115) or DEH (n = 11) by −4.0% body mass. Protinol™ (240, 280, and 320 mmol/kg) and Clinitrol™ (290 mmol/kg) reference solutions were compared similarly (n = 282 pairs). RESULTS: The 20 μL samples of plasma showed a 7 mmol/kg positive bias compared to 250 μL samples and displayed a nearly constant proportional error across the range tested (slope = 0.929). Calculated osmolarity was lower than 20 μL Posm by the same negative bias (−6.9 mmol/kg) but not different from 250 μL Posm (0.1 mmol/kg). The differences between 20 and 250 μL samples of Protinol™ were significantly higher than Clinitrol™. CONCLUSIONS: These results demonstrate that Posm measured by freezing point depression will be ~7 mmol/kg higher when using 20 μL vs 250 μL sample volumes. Approximately half of this effect may be due to plasma proteins. Posm sample volume should be carefully considered when calculating the osmole gap or assessing hydration status.